2021
DOI: 10.3390/pathogens10030339
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Human Coronavirus by FATHHOME’s Dry Sanitizer Device: Rapid and Eco-Friendly Ozone-Based Disinfection of SARS-CoV-2

Abstract: The pandemic of SARS-CoV-2/COVID-19 was reported in December 2019 in Wuhan, China. Pertaining to its high transmissibility and wide host adaptability, this unique human coronavirus spread across the planet inflicting 115 million people and causing 2.5 million deaths (as of March 3rd, 2021). Limited or negligible pre-existing immunity to multiple SARS-CoV-2 variants has resulted in severe morbidity and mortality worldwide, as well as a record-breaking surge in the use of medical-surgical supplies and personal p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Amongst all the reviewed and included studies, 28 articles were categorised in disinfection methods with potential activity on environmental surfaces [ 12 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ]. A summary of this category is provided in table II .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst all the reviewed and included studies, 28 articles were categorised in disinfection methods with potential activity on environmental surfaces [ 12 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ]. A summary of this category is provided in table II .…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of the same materials to higher concentrations of ozone was effective in reducing viral titres in a shorter period. Uppal et al demonstrated that ozone gas of at least 25ppm can optimally eliminate ≥99% of HCoV deposited on glass in 15 minutes while 80ppm of ozone and 90% relative humidity from another study obtained significant viral inactivation after 60 minutes [ 44 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since gaseous ozone treatment is inexpensive and easily accessible, it has become a widely used tool for the decontamination of offices, classrooms, and other public spaces during the COVID-19 pandemic. Up to this point, several studies investigated the efficiency of gaseous ozone treatment on coronavirus contaminated fomites [ 24 , 26 , 36 , 37 , 38 , 39 ]. However, all these experimental works were performed under strictly controlled laboratory conditions, with the application of airtight and low-volume chambers, which may not directly translate into a realistic environment [ 24 , 26 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Up to this point, several studies investigated the efficiency of gaseous ozone treatment on coronavirus contaminated fomites [ 24 , 26 , 36 , 37 , 38 , 39 ]. However, all these experimental works were performed under strictly controlled laboratory conditions, with the application of airtight and low-volume chambers, which may not directly translate into a realistic environment [ 24 , 26 , 37 , 38 , 39 ]. To our knowledge, this is the first report investigating the efficacy of gaseous ozone treatment against SARS-CoV-2 surrogate in conditions mimicking its actual use.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have also used HCoV-OC43 as a model to facilitate our understanding of the SARS-CoV-2, though they did not involve aerosolization. Uppal et al (2021) utilized HCoV-OC43 for testing the inactivation of human coronavirus on PPE and surfaces by a disinfection device. A low-cost method to titrate human coronavirus was developed by Bracci et al (2020) by utilizing both HCoV-OC43 and HCoV-229E.…”
Section: Introductionmentioning
confidence: 99%